(3GdedNU aj QSGdI EHWGd GdbjGS hGdQCi hGdJbdjOs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GHf MRe , CHh eMeOYdj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe,J (B456 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe CHh eMeO Ydi Hf CMeO Hf SYjO Hf MRe GdXGgQi bO CJe Gddg HeMeO Udi Gddg Ydjg hSde GdOjf hGSJhai Hg GdJHjjf s
(3BNQgG (B:s
(3bhdg LGeY ef GdeMGd GdHGWd Cf jchf Gddg jCeQfG HGdbjGS Ch HGdJYdjd Ch HGdQCi dCf gPG Jcdja eG djS ai GdhSY hHGddg GdJhajb ced GdedNU ef QSGdI EHWGd GdbjGS hGdQCi hGdJbdjO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs